Does Brazil need a new AIDS agenda? - Chequer, Pedro (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Since the 90’s Brazil has the characterized of basing its public policies to address HIV/AIDS in scientific evidence; to this ingre-dient, it has added up the democratic and inclusive participatory process, and civil society has played an important role, providing criticisms, suggestions, successful pilot experiences and a peer education agenda, being present in circumstances where public services are neither competent nor accessible to provide a more inclusive, compassionate and appropriate care. [...]